Congenital bilateral upper lid eversion - Almajed, Faten; Alsulaiman, Hamad; Almadhi, Nada; Schellini, Silvana [UNESP]; Sesma, Gorka (Wolters Kluwer, 2020)
We report two healthy Saudi newborns with congenital bilateral upper lid eversion evolving with good outcome using conservative treatment. The current literature including epidemiology, clinical characteristics, possible etiologic factors, and treatment was reviewed.
Keywords: Congenital ectropion; conjunctival chemosis; upper lid eversion